ANALISIS PENERAPAN SISTEM TRANSAKSI NON TUNAI DALAM PENGELOLAAN KEUANGAN DAERAH PADA DINAS LINGKUNGAN HIDUP KOTA BITUNG - Pelealu, Angelina; Nangoi, Grace B.; Gerungai, Natalia Y. T. (Universitas Sam Ratulangi, 2018)
In an effort to improve an efficient regional financial management system, the government issued the Minister of Home Affairs Circular No. 910/1866 / SJ concerning the Implementation of Non-Cash Transactions on April 17, 2017, which is in accordance with the Provisions of Article 283 paragraph (2) of Act Number 23 of 2014 and in accordance with Presidential Instruction Number 10 of 2016 concerning Prevention and Eradication of Corruption. Non-cash transactions are transactions that do not make payments in cash but by way of transfer or transfer between accounts from one party to another. The purpose of this study is to determine the readiness of the process of implementing a non-cash transaction system in the management of regional finances in the Bitung City Environment Agency and to find out what obstacles occur in the process of implementing non-cash transactions in regional financial management in the Bitung City Environmental Service. The research method used is qualitative descriptive. The results of the research, namely the Environmental Office of the city of Bitung has implemented a system of non-cash transactions in stages in the APBD based on Circular of the Minister of Home Affairs No. 910/1866 / SJ. The constraints faced are the administrative process sometimes hampered, the socialization process, its application to the receipt of levies with a small nominal value.Keywords: Analysis, Implementation of Non-Cash Transaction System, Regional Financial Management